2003
DOI: 10.1038/sj.sc.3101399
|View full text |Cite
|
Sign up to set email alerts
|

Experience of tension-free vaginal tape for the treatment of stress incontinence in females with neuropathic bladders

Abstract: Study design: Retrospective. Objective: To evaluate the safety and e cacy of the tension-free vaginal tape (TVT) for the treatment of stress incontinence in females with neuropathic bladders. Setting: London Spinal Injuries Unit, Stanmore & Institute of Urology, London, UK. Methods: Twelve women (mean age 53.3 years; range 41 ± 80 years) with neuropathic bladder dysfunction and stress urinary incontinence were treated with tension-free vaginal tape (TVT) between November 1997 and December 2000. The group consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Our results also compare favourably to previously reported success rates with tension-free vaginal tape, 4,5,15,16 with success rates at least as great with longer follow-up in our study. Furthermore, our results are comparable to those achieved in the general population undergoing TOT surgery.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results also compare favourably to previously reported success rates with tension-free vaginal tape, 4,5,15,16 with success rates at least as great with longer follow-up in our study. Furthermore, our results are comparable to those achieved in the general population undergoing TOT surgery.…”
Section: Discussionsupporting
confidence: 81%
“…4,5 This showed success comparable to non-neuropaths in both short and long term with few complications. The aim of this study was to present the first series of long-term safety and efficacy outcomes of placement of mid-urethral synthetic transobturator tapes (TOT) in patients with urodynamically confirmed SUI and NBD due to SCI.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…All four patients (two with SS-SCL and two with IS-SCL), previously treated with bulking agents, underwent the TVT procedure, when SUI occurred again after a second sphincter injection. 8,9 The only patient with IS-SCL who previously emptied her bladder spontaneously started AIC regimen after TVT surgery. A reduction of around 90% in SUI compared with baseline was maintained up to the final follow-up at around 6 years.…”
Section: Stress Urinary Incontinence Treatment: Bulking Agent Four Fmentioning
confidence: 99%
“…This result confirms previous positive findings in literature; therefore, TVT surgery should be part of the neuro-urologist's surgical armamentarium. 8,9 It was worth saying that at the time of patient inclusion in the studies, literature had not reported any data concerning, for example, the efficacy/safety of repetitive use of BoNT-A on SCL patients for NOB who were unresponsive to antimuscarinics or the use of SNM on subjects with SCL suffering from N-LUTD.…”
mentioning
confidence: 99%